EVALUATION OF THE IMPACT OF ELECTRON DENSITY CONVERSION DATASET ON DOSE CALCULATION IN RADIOTHERAPY TREATMENT PLANNING FOR CANCER PATIENTS AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the impact of an institution-specific CT-to-relative electron density (CT-ED) calibration dataset on dose distribution in intensity-modulated radiation therapy (IMRT) treatment plans calculated using the Monte Carlo algorithm in the Monaco 5.11 treatment planning system.Đối tượng và phương pháp: A retrospective study was conducted on 120 clinically approved IMRT treatment plans, including 40 patients with nasopharyngeal cancer, 40 with lung cancer, and 40 with rectal cancer. An institution-specific CT-ED dataset was established using an Advanced Electron Density Phantom scanned on a Discovery RT CT simulator. Each treatment plan was recalculated using the calibrated CT-ED dataset while maintaining all planning parameters unchanged except for the CT-ED conversion dataset. Dosimetric parameters of the planning target volume (PTV), organs at risk, conformity index (CI), and Gamma Index were compared between the original and recalculated plans.Results: Compared with the manufacturer’s default CT-ED dataset, the institution-specific calibration dataset showed Hounsfield Unit (HU) differences of 49-63 HU in low-density materials and was subsequently implemented in the Monaco 5.11 treatment planning system. Recalculation using the calibrated CT-ED dataset resulted in statistically significant differences in most dosimetric parameters (p < 0.05), although the absolute changes were generally less than 2%. Most head-and-neck and thoracic treatment plans demonstrated PTV differences below 1%, whereas pelvic plans showed greater variation, with 57.5% exhibiting PTV differences of ≥ 2%. The mean Gamma passing rates ranged from 97-97.7% using the 2%/2 mm criterion and exceeded 99.5% using the 3%/3 mm criterion, remaining above the accepted clinical thresholdConclusions: The institution-specific CT-ED calibration dataset produced small but statistically significant changes in IMRT dose distribution, while all treatment plans continued to satisfy the dose constraints recommended by the RTOG and eviQ guidelines. These findings support the routine establishment and periodic verification of institution-specific CT-ED datasets for individual CT simulators to ensure consistent and reliable dose calculation in radiotherapy.
Keywords: CT-ED, Hounsfield Unit, relative electron density, Monte Carlo, IMRT, Monaco 5.11.